2017
DOI: 10.1007/s40265-017-0712-6
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Appropriate Use of Over-the-Counter Proton Pump Inhibitors: An Evidence-Based Review and Delphi Consensus

Abstract: The availability of over-the-counter (OTC) proton pump inhibitors (PPIs) for the short-term (2 weeks) management of frequent heartburn (≥2 days/week) has increased markedly, yet evidence-based recommendations have not been developed. A panel of nine international experts in gastroesophageal reflux disease developed consensus statements regarding the risks and benefits of OTC PPIs using a modified Delphi process. Consensus (based on ≥80% approval) was reached through multiple rounds of remote voting and a final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 170 publications
0
39
0
2
Order By: Relevance
“…Common PPIs include omeprazole, esomeprazole, lansoprazole, dexlansoprazole, pantoprazole, and rabeprazole, with many of these being available without a prescription [2,[10][11][12][36][37][38]. PPIs irreversibly bind and inactivate the proton pump (i.e., the hydrogen/potassium adenosine triphosphatase system) at the secretory surface of gastric parietal cells.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common PPIs include omeprazole, esomeprazole, lansoprazole, dexlansoprazole, pantoprazole, and rabeprazole, with many of these being available without a prescription [2,[10][11][12][36][37][38]. PPIs irreversibly bind and inactivate the proton pump (i.e., the hydrogen/potassium adenosine triphosphatase system) at the secretory surface of gastric parietal cells.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…Although several review articles have been published discussing gastric acid-related DDIs mediated by coadministration of antacids [1], H 2 RAs [9], or PPIs [2,[10][11][12], these reviews are not sufficiently comprehensive in capturing all documented DDIs with ARAs and tend to focus on gastric pH-dependent DDIs and/or basic drugs. Subsequently, several new drugs have been approved, and new information is available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of PPIs as an OTC drug and it's over utilization by common and normal people for multiple disease backgrounds with or without symptoms has subjected patients to a potential risk such as parietal cell hypertrophy, enterochromaffin like cell hyperplasia and hypergastrinemia leading to rebound acid secretion. 2 To avoid this to happen, there needs to be a contemplation on how to best use these agents safely and effectively. Additionally, there is a need for guidelines for pharmacy use to assist with safe and effective treatment of reflux symptoms with OTC PPIs and lastly, patient education and awareness is a must 10 as most of them end up selfmedicating themselves.…”
Section: Specific Problemmentioning
confidence: 99%
“…PPI therapy does treat some symptoms of GERD but not its cause. Even if these symptoms respond to medical therapy, PPIs have come under scrutiny due to eventual long‐term adverse events . Although several clinical studies have shown a cancer‐protective effect of PPI, data remain contradictory .…”
Section: Introductionmentioning
confidence: 99%
“…Even if these symptoms respond to medical therapy, PPIs have come under scrutiny due to eventual long-term adverse events. 2 Although several clinical studies have shown a cancer-protective effect of PPI, data remain contradictory. 3 As apparently only a very small proportion of GERD patients are finally treated by conventional antireflux surgery, a large therapeutic window of patients, who are not effectively treated with PPI but do not want to run the potential risks of conventional surgery, remains.…”
Section: Introductionmentioning
confidence: 99%